The Vilnius issue in international relations: the historiography of the problem - Mankevich Maria (Baltic Region, 2012)
This article considers certain historiographical aspects of the Vilnius issue as an international problem. The author analyses the origins of the Polish-Lithuanian conflict, the role of the struggle for Vilnius in the general context of the Polish-Lithuanian confrontation, and the origin and nature of Lithuanian nationalism. The article also examines historiographical perspectives on the seizure of Vilnius by the troops of the Polish general, L. Żeligowsky, and the international consequences of the violation of the Suwałki Agreement. The author pays special attention to the positions of western powers, the decision of the Conference of Ambassadors on March 15, 1923, and the mediation of the League of Nations in the territorial dispute between Lithuania and Poland. The article considers the existing historiographical concepts and evaluations of the role of the Soviet diplomacy in the Vilnius issue. The author identifies new trends in the contemporary historiography of the Vilnius problem.